HISTOLOGIC AND ELECTRON MICROSCOPIC PERIAPICAL TISSUE EXAMINATION RESULTS IN TEETH WITH CHRONIC APICAL PERIODONTITIS. - Angela Gusiyska (Peytchinski Publishing, 2014)
Introduction: Key stages in the treatment of chronic apical periodontitis (CAP) are the assessment of the status of periapical zone, effective decontamination and subsequent sealing of the root canal space. Purpose: The aim of this article is to analyze histologic and electron microscopic results from periapical tissue examination in teeth with chronic apical periodontitis. Material and Methods: The apices of 43 teeth (n = 43) were examined, allocated in two groups. The teeth were stored in saline solution (9% NaCl) supplemented with thymol, at 4°C. The apical portions of the roots were resected at 5 mm coronary. After resection, the apices were fixed to stands for SEM-examination. The periapical lesions (n = 24) were carefully removed with a curette from the root or the apical portion of the alveolar socket and were kept in 10% formalin solution to the preparation of histological samples. Results and Discussion: The results of the performed SEM-examinations of the apical zones showed that in 97.6% of the teeth with radiographically diagnosed CAP, there were external resorption around the apical foramen and associated apertures of varying degrees - from the initial to the advanced stage of apical resorption. Despite the limited number of examined cases, the results obtained confirm the histology and the inaccuracy of diagnostic assumptions in some of the cases, resultant from the radiographic examination only Conclusion: Based on the analysis of results, the following conclusions can be drawn: that external resorption around the apical foramen is established in 97.6% of cases in the teeth with radiographically diagnosed CAP.